Risk Factors for Stunting Among Children: A Community Based Case Control Study in Nepal - Paudel, Rajan; Pradhan, B; Wagle, RR; Pahari, DP; Onta, SR (Kathmandu University Medical Journal, 2013)
Background Stunting, a chronic condition, is an underlying cause of child morbidity and mortality in Nepal. This study intends to identify the factors causing stunting among children that will help to prioritize the strategies at the district level. Objective The objective of the study was to identify the risk factors for stunting among children of age between 6 to 59 months. Methods The study was based on community-based case control design in the mid-west, Surkhet Nepal from August to September 2010. The cases were stunted children and controls were the children without stunting. Data was collected by interviewing those children’s mothers and measured length/height of 118 children as cases and 236 children as controls. Logistic regression analysis was performed to identify the best model of factors leading to stunting. Odds ratio and 95% confidence interval were used as a measure of association. Results Socio-economic risk factors for stunting comprised mothers without earning (OR=3.11, 95% CI 1.26-7.65), food deficit families (OR=4.26, 95% CI 1.73-10.45) and care taker of the children other than mother (OR=3.02, 95% CI 1.19-7.70). Environmental risk factors for stunting consisted of kitchen without ventilation and children exposed to pesticide. Inappropriate exclusive breast feeding (OR=6.90, 95% CI 2.81-16.97), complementary feeding less than four times a day (OR=3.60, 95% CI 1.32-9.95) and dietary diversity below WHO standard (OR=4.06, 95% CI 1.70-9.67) were factors of stunted children. Diarrhea was found significantly associated with stunting (OR=7.46, 95% CI 2.98-18.65). Conclusions Stunting was found to be as a result of multiple factors such as socio-economic, environmental and inappropriate feeding practices. Kathmandu University Medical Journal | VOL.10 | NO. 3 | ISSUE 39 | JUL- SEP 2012 | Page 18-24 DOI: http://dx.doi.org/10.3126/kumj.v10i3.8012